Bogart - Ursini, James; Duncan, Paul (Germany : Taschen, 2007)
Biography of actor Humphrey Bogart, discussing his early life as the child of a wealthy New York surgeon and a successful portrait painter, looking at his first roles in Broadway plays, tracing his film career, and following his personal struggles to find happiness.
Includes bibliographical references.
Adult.
Adult
Keywords: Bogart, Humphrey, -- 1899-1957.; Motion picture actors and actresses -- United States -- Biography; Actors -- United States -- Biography